Effect of KRAS exon 2 mutations on antitumor activity of afatinib and gefitinib. Issue 4 (April 2015) - Gamba, Sebastian; Camaj, Peter; Heinemann, Volker; Laubender, Rüdiger P.; Wang, Yan; Zhao, Yue; Stintzing, Sebastian; Giessen, Clemens; Boeck, Stefan; Haertl, Christoph; Bruns, Christiane J.; Modest, Dominik P.
Abstract : The aim of this study was to investigate the impact of different KRAS mutations on the inhibitory potential of afatinib and gefitinib in SW48 colorectal cancer cells. The influence of afatinib/gefitinib on cell viability and cell cycle was evaluated in isogenic SW48 KRAS wild-type/mutant cells. Protein levels of phosphorylated/total EGFR, HER-2, HER-3, ERK, and AKT were compared between treated/untreated samples using western blotting. The activity of both afatinib and gefitinib was the lowest in KRAS G12C/G12S/G12D and the highest in G13D/G12A mutant subtypes. A 50% decrease in cell viability was achieved at concentrations of 3.0–7.7 μmol/l for afatinib and 5.4–19.5 μmol/l for gefitinib. The effect of both drugs on apoptosis appeared to be stronger than their influence on proliferation and was generally less pronounced in mutant cells than in wild-type cells. The average number of apoptotic cells after treatment with afatinib was 2.6 times as high as the corresponding value following treatment with gefitinib ( P <0.01). Levels of pEGFR, pHER-2, pERK, and pAKT were reduced more extensively by afatinib than by gefitinib ( P <0.001). Some KRAS mutations (G12C/G12S/G12D) appear to weaken the activity of afatinib and gefitinib whereas others seem to increase sensitivity to treatment (G13D/G12A) compared with the parental clone ( KRAS wild-type). In SW48 colorectal cancer cells, afatinib seems to be more potent than gefitinib because of its superior efficacy in inhibiting both EGFR and HER-2, suppressing signaling along both MEK/ERK and PI3K/AKT pathways to a greater extent.